Determinant Factors of Surplus (Deficit) Underwriting in Sharia Life Insurance in Indonesia - sa'adah tri hayatun; Ai Nur Bayinah; Mustafa Kamal (IQTISHADIA, 2022)
This study aims to investigate the determining factors of surplus (deficit) underwriting in sharia life insurance in Indonesia. The factors considered are net contribution, claims, and investment return. The study employed panel data regression, using a sample of 15 sharia life insurance companies, including 12 sharia business units and 3 full sharia companies, over the period of 2015-2018. Analysis of the data suggests that Random Effect Model (REM) is the most appropriate estimation model for this study. Results indicate that net contribution and claim variables have a significant partial effect on surplus (deficit) underwriting, while the investment return does not. The study also found that all of independent variables (net contribution, claim, and investment result) have a significant simultaneous effect on the surplus (deficit) underwriting.